The Palgrave Handbook of Ageing and Physical Activity Promotion 2018
DOI: 10.1007/978-3-319-71291-8_22
|View full text |Cite|
|
Sign up to set email alerts
|

Physical Environments That Promote Physical Activity Among Older People

Abstract: Characteristics of neighbourhoods, streets and public open spaces can hinder or facilitate physical activity (PA) among older adults. This chapter aims to critically review key conceptual and theoretical frameworks and the empirical evidence about the relationships between aspects of the physical environment and older adults' PA. Access to local shops, services, public transport, public open spaces (e.g., parks), and recreational facilities within walking distance along well-maintained and aesthetically-pleasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Such indices capture the extent to which a built environmental setting supports the act of walking derived through a geographical information system (GIS) [18]. Although there is no universal operationalization, walkability indices usually consider a neighborhood’s land-use mix (i.e., the diversity of land uses), street connectivity (i.e., the directness of streets and the availability of alternative routes), and residential density (i.e., the number of residents) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such indices capture the extent to which a built environmental setting supports the act of walking derived through a geographical information system (GIS) [18]. Although there is no universal operationalization, walkability indices usually consider a neighborhood’s land-use mix (i.e., the diversity of land uses), street connectivity (i.e., the directness of streets and the availability of alternative routes), and residential density (i.e., the number of residents) [19].…”
Section: Introductionmentioning
confidence: 99%
“…26 Reviews synthesizing built environment and PA studies conducted among older adults have generally found similar evidence of higher walkability and access to recreational facilities can promote PA in this population group as well. [27][28][29][30] More importantly, a small number of studies have investigated the associations between built environment attributes and PA among patients with CVD. For instance, a Japanese study found positive associations of the presence of sidewalks and access to recreational facilities with levels of walking among stroke survivors.…”
Section: Built Environment and Physical Activitymentioning
confidence: 99%